2011
DOI: 10.1068/p6879
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Weight Judgments When Viewing One's Own and others' Movements under Minimalist Conditions of Visual Presentation

Abstract: Across five experiments, we investigated the parameters involved in the observation and in the execution of the action of lifting an object. The observers were shown minimal information on movements, consisting of either the working-point displacement only (ie two points representing the hand and object) or additional configural information on the kinematics of the trunk, shoulder, arm, forearm, and hand, joined by a stick diagram. Furthermore, displays showed either a participant's own movements or those of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…This distinction was made to see whether inter-joint coordination and trunk movements provide important kinematic information, or whether end-point characteristics alone are suYcient to perceive qualitative information about movement execution. For a detailed description of display constructions, see Auvray et al (2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This distinction was made to see whether inter-joint coordination and trunk movements provide important kinematic information, or whether end-point characteristics alone are suYcient to perceive qualitative information about movement execution. For a detailed description of display constructions, see Auvray et al (2011).…”
Section: Methodsmentioning
confidence: 99%
“…Responses on the visual-analogue scale were analysed according to the level of impairment of the observed Auvray et al (2011), the following kinematic cues were expected to inXuence the perception of movement Xuency: (a) movement time (start and endpoint of movement were deWned with a velocity threshold of 0.1 m/s), (b) distance between start and endpoint, (c) mean velocity of the hand, (d) peak velocity of the hand, (e) ratio between the mean and peak velocity, (f) number of velocity peaks (Wlter: Wrst order low pass Butterworth, cut-oV 6 Hz), (g) trunk rotation (rotation angle C7 to starting point T8), (h) trunk displacement (horizontal displacement C7), (i) curvature index (ratio trajectory/distance), and (j) curvature diVerence (trajectory minus distance).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…For example, Hamilton et al ( 2007 ) demonstrated that the most reliable physical cues as to the weight of a lifted item do not correspond to the perceptual cues that individuals use when making a weight judgment. Auvray et al ( 2011 ) observed similar discrepancies and suggest that individuals do not engage an “exact copy” of action execution when making perceptual judgments, but rather exploit the most diagnostic visual cues, such as acceleration. Indeed, motion cues such as velocity and acceleration can be used to determine the weight of lifted objects even when visual information is only provided by moving point light displays (Shim and Carlton, 1997 ).…”
Section: Introductionmentioning
confidence: 95%
“…Since the pioneering studies of Johansson (1973 , 1976 ), several aspects of biological movement perception have been investigated, allowing researchers to demonstrate that relatively few visual and/or auditory cues are sufficient to evoke accurate representation of complex movements and for participants to be able to discriminate among various characteristics of perceived events (e.g., type of activity, performer, gender, emotions; Barclay et al, 1978 ; Repp, 1987 ; Dittrich et al, 1996 ; Flach et al, 2004 ; Loula et al, 2005 ; Auvray et al, 2011 ; Hohmann et al, 2011 ; Sevdalis and Keller, 2011 ; Murgia et al, 2012 ; Kennel et al, 2014 ). Overall, based on previous studies, it seems that a crucial factor for accurate biological movement perception is the perceptual-motor experience of the observer ( Abernethy et al, 2001 ; Repp and Knoblich, 2004 ; Mann et al, 2007 ; Hohmann et al, 2011 ; Tomeo et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%